7. STATUS OF COVID-19 PREVENTION IN QUANG NAM PROVINCE IN 2020-2021 (Vietnam Journal of Community Medicine, 2023)
COVID-19 pandemic situation: The COVID-19 pandemic was first detected in China in December2019 and quickly entered Vietnam. Quang Nam is one of the provinces heavily affected by thepandemic. However, Quang Nam has achieved remarkable results with a proactive and drastic spiritin pandemic prevention and control.Methodology: A cross-sectional study using data on the number of people isolated, the number ofsamples tested, and the number of COVID-19 vaccine shots were conducted in Quang Nam.Results: Isolate 80,357 people to prevent the pandemic from spreading, of which: 10,539 people in2020 (13.1%) and 69,818 people in 2021 (86.9%); Testing capacity was increasingly improved with701,248 test samples taken, of which 102,267 test samples in 2020 (14.6%) and 598,981 samplesin 2021 (85.4%); The rate of people aged 18 years and over receiving at least one shot of vaccinereached 99.1%, the number of people receiving the full bare shot got 86.8%, the number of peoplewho received the booster shot advanced 0.1%, the results of vaccination for children aged 12-17needing to be vaccinated 86.1%.Conclusions: Quang Nam’s epidemic prevention and control activities in the two years 2020-2021focused on three main activities: isolating to prevent the spread of the disease, testing to detect casesand covering vaccination for people.
Keywords: COVID - 19, Vietnam, Quang Nam province, COVID - 19 vaccines, COVID - 19 testing.